PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KECERDASAN EMOSIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Armianus Randing; Syamsul Hadi; Eko Yulianto (Universitas Bina Taruna Gorontalo, 2023)
This study aims to examine and analyze the influence of the variables Transformational Leadership Style, Emotional Intelligence, Organizational Commitment on Employee Performance mediated by Job Satisfaction. Case study on the DIY Regional Disaster Management Agency (BPBD). The population in this study amounted to 45 people. The sampling technique used the saturated or census sampling method, totaling 45 people. This research method uses descriptive analysis by evaluating the measurement model (out model), structural model (inner model) and the results of hypothesis testing test the hypothesis directly output images and values ​​contained in the output path coefficients. Data processing uses smartPLS (v.3.2.9). The results of this study indicate that transformational leadership style and emotional intelligence have no significant effect on employee performance, because the value is less than 1,960, while the organizational mindset and job satisfaction have a significant effect on employee performance with a value of more than 1,960. The variables of transformational leadership style, emotional intelligence and organizational trust in employee performance which are mediated by job satisfaction are both significantly affected with a value of more than 1,960. The head of the Yogyakarta Regional Disaster Management Agency (BPBD) office needs to provide motivation to employees so that the company's vision and mission are achieved. Employees need to pay attention to emotional intelligence variables with indicators such as self-awareness, self-management, self-motivation, empathy and social skills (relationship management).